2006
DOI: 10.1037/0033-295x.113.4.766
|View full text |Cite
|
Sign up to set email alerts
|

Contextual guidance of eye movements and attention in real-world scenes: The role of global features in object search.

Abstract: Many experiments have shown that the human visual system makes extensive use of contextual information for facilitating object search in natural scenes. However, the question of how to formally model contextual influences is still open. On the basis of a Bayesian framework, the authors present an original approach of attentional guidance by global scene context. The model comprises 2 parallel pathways; one pathway computes local features (saliency) and the other computes global (scenecentered) features. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
1,382
4
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,458 publications
(1,443 citation statements)
references
References 132 publications
(205 reference statements)
52
1,382
4
5
Order By: Relevance
“…Given that scene gist recognition occurs within a single eye fixation (Eckstein et al, 2006;Torralba et al, 2006), and that fixation durations are generally tied to the processing times required for various visual recognition tasks (Nuthmann, Smith, Engbert, & Henderson, 2010;Rayner, 1998), it seems a reasonable assumption that pigeons may both require longer stimulus durations to recognize gist and tend make longer fixation durations than humans, both by roughly an order of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Given that scene gist recognition occurs within a single eye fixation (Eckstein et al, 2006;Torralba et al, 2006), and that fixation durations are generally tied to the processing times required for various visual recognition tasks (Nuthmann, Smith, Engbert, & Henderson, 2010;Rayner, 1998), it seems a reasonable assumption that pigeons may both require longer stimulus durations to recognize gist and tend make longer fixation durations than humans, both by roughly an order of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…These authors noted that traditional models of eye movements (e.g., Itti & Koch, 2000;Torralba, Oliva, Castelhano & Henderson, 2006) fail to account for the influence of a preceding, but unrelated task when the information is not beneficial to the secondary task (i.e., exposure to a different scene or situation). As a result, the mechanisms that underlie this negative carry over effect are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Torralba et al (2006) and Zhang and Cottrell (submitted) have also suggested that saliency should reflect target probability, although they propose approaches to computing the target probability very different from ours. Our approach is to compute the target probability using statistics obtained from recent experience performing the task.…”
Section: Experience-guided Searchmentioning
confidence: 87%